The healing - Brunstetter, Wanda E. (Uhrichsville, OH : Barbour Pub., Inc., 2011)
Can a man burdened by memories of yesterday find hope in the land of tomorrow? Will peace-loving Samuel and Esther fight for their newfound love? How will God manage to untangle these star-crossed lovers before any damage is done?
Keywords: Single men -- Fiction; Amish -- Fiction; Kentucky -- Fiction; Love stories; Christian fiction